On Reliability and Validity - Martins, Gilberto de Andrade (Review of Business Management, 2007)
In order to assess, evaluate or quantify financial, equity, auditing and controllership oriented data related both to private and public sectors, the practioner or the researcher has to pay close attention to the significance and accurateness criteria of the research tools he is about to employ: validity and reliability. The validity criterion refers to the instrument capacity of assessing what it intends to assess; reliability deals with the constancy of results when the same individual or object is assessed, evaluated or quantified more than once. This article is aimed at explaining and discussing examples of proper criteria to indicate the reliability level: test-retest, equivalent form techniques, split-half, reliability based on evaluators, Cronbach´s alpha coefficient, as well as techniques towards validity evaluation: apparent validity, content validity, criterion validity, construct and total validity. Different illustrations of the criteria for assessing validity and reliability in the Accounting field are shown. Key-words: Reliability. Validity. Measures. Accounting. Assessment.